STUDI POTENSI LAHAN DAN AREA PERUMAHAN UNTUK IMPLEMENTASI PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) DI WILAYAH SERANG DAN CILEGON BANTEN - Suhendar Suhendar; Budi Raharjo; Alimuddin Alimuddin; Hady Sutjipto (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2016)
Electrical energy requirements increase as population growth and technological development. Increased triggered also by the rate of energy demand growth of 6.86% annually. Energy needs largely derived from non-renewable energy which has its limitations and is not environmentally friendly. Therefore we need a renewable energy alternative and environmentally friendly. One such alternative is the use of solar energy as a power plant that was converted by solar panels. To do with it, this study aims to determine the potential for, contributions and aspects of the cost of solar energy as a power plant in a residential neighborhood Serang Cilegon. The results showed that the development and implementation of SPP in an open area can generate a total capacity 84971.481 kWp. The greatest potential in the residential Highland Park with a capacity of 50370.802 kWp that have an energy conversion amounted to 36,707,706 kWh / year. While the supply of energy 33750047 kWh / year will be able to contribute to meet all the needs of the household burden. While in Pondok Cilegon Indah residential area with a capacity of 123.032 kWp with a conversion of energy 98387 kWh / year. Energy supply 90 452 kWh / year to contribute 0.76% of the burden of households. PLTS investment with life project for 25 years for a return on investment costs takes as long as 25 years and 1 month as of the beginning of the project so as not feasible investment.